Developing radical innovation in telecommunications: an R&D management perspective - Song, Rui (2015)
Radical innovation has been identified as one of the central topics of innovation management, being relevant to the development process, the categories, and the R&D department’s responsibilities for development. Based on the above three individual research conversations, this research aimed to determine, when the R&D department of a large telecommunications operator engaged in radical innovation, which capabilities they used and how the use of these capabilities was affected by different contextual factors at each stage of the radical innovation development cycle. By comparing the aim of the current research with other researchers’ findings on relevant topics, three gaps in the research were identified, and two research questions were raised, as below: